Cellulose Filaments for Responsive and Functional Materials - Almeida, Ana Patrícia Correia (2021)
Cellulosic filaments, found in plants, are crucial structural elements for their survival and are a great source of inspiration to obtain new functional materials. The work performed out in this thesis aimed for the isolation, physical characterization, study of the morphology and shape, as well as the mechanical behaviour of cellulosic filaments obtained from the leaves of Agapanthus africanus and Ornithogalum thyrsoides and from the filaments that form the ribbons existing on the awns of the Erodium plants. These cellulosic filaments and filament networks were chosen due to the fundamental role that they play in the plant kingdom and their ability to change shape in the presence of an external stimuli. The study of the chosen systems served as an inspiration for the preparation and production of new membranes formed by non-woven networks of micro/nano filaments. A prototype, which allows for the selective removal of oil micro droplets from aqueous emulsions, was developed. This dissertation begins with a general introduction, based on two review papers, which the author of this thesis is the first author, in which the main concepts used in the following chapters are addressed and interconnected. The original part of the work is in chapters II, III and IV. In chapter II, the study of microfilaments from the leaves tracheary of two plants, Agapanthus africanus and Ornithogalum thyrsoides, is made. These microfilaments belong to plants of the same order and have identical shapes (left helices), chemical composition and skeletons, but different mechanical properties. For the first time, micrometric droplets of a nematic liquid crystal were used as sensors to reveal the morphology of the filaments. In order to obtain quantitative characteristics on the surface of the microfilaments, photos of the textures of pierced droplets were obtained by Polarized Optical Microscopy (POM). These textures were compared with simulated optical microphotographs obtained by numerical modelling for the nematic droplets. Homeotropic anchoring at the air, and different anchoring conditions, at the interfaces with the filaments were considered for the nematic structure. This study allowed the establishment of relationships between the physical properties/morphology of the filaments and to determine their interactions with other filaments and with the environment. In chapter III, cellulosic networks existing on dead tissues of the Erodium awns were isolated and characterized. An interesting feature of these cellulosic networks is that they form ribbons that change reversibly the shape in the presence of moisture. When dried these ribbons are right-handed helices, that uncoil remaining taut, in the presence of moisture. The work performed allowed the preparation of helical ribbons that can change the shape from right- to lefthanded helices in the presence of moisture. The behaviour observed was explained using computational simulations, considering filaments that contract and expand asymmetrically. Birefringent transparent ribbons were also isolated. The asymmetric arrangement of cellulosic fibres allows the material to be stimuli-responsive without the use of complicated lithography and intricate deposition techniques, making it suitable for a diverse range of applications, such as the production of intelligent textiles and environmental friendly micro components. In chapter IV, non-woven membranes obtained from cellulosic materials and cellulose nanocrystals were prepared and characterized. Different patterns were designed using the screenprinting technique. The adhesion between the different types of cellulosic fibres was promoted through a heat treatment. The non-woven membranes produced allowed the development of a prototype that selectively removes oil droplets from aqueous emulsions with an efficiency of approximately 80%. Throughout this thesis (chapters II and III), the complexity of the systems increases. The work begins by studying the morphology of a filament and its mechanical behaviour in the presence of other filaments. After a much more complex system, in which anisotropic filament networks, produced by the Erodium plant were addressed. The stimuli-responsive behaviour of these anisotropic networks was investigated after being released by the plant. Based on the understanding of the systems formed by cellulosic filaments, studied in chapters II and III, functional non-woven membranes were produced, printed, and characterized. The non-woven membranes led to the development of a prototype, which allows the selective removal of micro droplets of oil form aqueous emulsions. At the end, a summary of the main scientific results and future work including a technological application, which was developed in the framework of this thesis, are presented.